Solve v + 5 = -2*z, 8*v + 3*z + 4 = 3*v for v.

1

Solve -4*i + 18 = -2*c, -4*i + 9 = c - 0*c for c.

-3

Solve 8*y - 6*y = -4*w - 8, 0 = -2*w - 3*y - 8 for w.

-1

Solve -5*v + 1134*q = 1131*q - 34, 2*v - 13 = q for v.

5

Solve 2*v - 5*n = 375 - 345, -2 = n for v.

10

Solve 5*s - f = -4*f + 16, 3*s - 8 = -f for s.

2

Solve -5*p - f + 22 = 0, -p - 283 = 4*f - 276 for p.

5

Solve 2*z + 3 + 1 = -4*s, 25 = -3*s + 4*z for s.

-3

Solve -4*c + 4*f = 40, 0 = -7*c + 2*c + 3*f - 40 for c.

-5

Solve -3*i + 5 + 5 = -p, 0 = p + 2*i - 5 for p.

-1